The Influence of Using Social Networks (Twitter) on Asocial Attitudes in Pustek Serpong Vocational School Students - Haiqal Al Faroby; Anggi Dimas Koswara; Sri Bintang Agustiana; Abdul Basit (Persepsi: Communication Journal, 2023)
Influence of Social Networking Twitter Against Antisocial Attitudes on Students of SMK Pustek Serpong. Department of Communication Studies, Faculty of Social and Political Sciences. 2021. The use of social networking site Twitter is currently growing among teenagers. This can cause a variety of changes in attitudes among the students themselves. The purpose of this study was to determine how the effect of the use of social networking twitter against antisocial behavior in SMK Pustek in terms of cognitive, affective, conative. This research was supported by the theory that media dependency theory, in which the current media has an influence on the formation of attitudes to someone who continues to use social media in their daily life. Researchers used a quantitative approach to study the nature of explanative. Data collection techniques used to distribute questionnaires. The samples in this study were SMK Pustek Serpong with sampling probability sampling technique. The results showed a correlation between the use of social networking towards asocial attitudes in students at 80.2%. The influence of social networking twitter use has contributed greatly to the asocial attitudes obtained from the calculation of the coefficient of determination is equal to 64.2%. When viewed from the side of the attitude which consists of cognitive, affective, conative, the attitude of the students in terms of conative where most of the students have a tendency to always use social media for personal use. In terms of cognitive (knowledge) and affective (feeling) also received a positive response from the majority of students of SMK Pustek Serpong. Outcome data in the can that is significant and valid..